(untitled) (CSIAM Transactions on Applied Mathematics, 2024)
In this paper, we consider the global well-posedness of solutions to a parabolic-parabolic Keller-Segel model with p-Laplace diffusion. We first establish a critical exponent p^∗=3N/(N+1) and prove that when p> p^∗, the solution exists globally for arbitrary large initial value. When 1